Penerapan Metode TOPSIS Dalam Perekrutan Calon Karyawan - Gde Iwan Setiawan; I Putu Eka Indrawan (Journal of Information System Research (JOSH), 2023)
A company is said to be successful if it has a successful Human Resource Department (HRD) section based on the attitudes and skills possessed. Recruitment is the most important activity in human resource management, namely to get the right people for the company. To achieve company goals effectively and efficiently, competent and skilled employees are needed and the quality and quantity are in accordance with company needs. Determination of prospective employees to be recruited is adjusted to several criteria that influence each other, so we need a system that can help make decisions in recruiting the right and quality new employee candidates. The method used in recruiting candidates is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method, namely the MADM (Multiple-Attribute Decision Making) model. This method is used to determine the best choice from a number of alternatives, where a good chosen alternative does not only have the shortest distance from the positive ideal solution. This system was built using the PHP programming language with MySQL database. With this web-based system, applicants can register for job vacancies according to the needs of the company so that the end result is in the form of an ideal alternative report based on the ranking of the TOPSIS method and the number of prospective employees to be recruited to fill vacancies at PT. Telkom Access Denpasar.